Motivasi Penggemar K-Pop sebagai Citizen Author Menulis Fan Fiction - Qoryna Noer Seyma El Farabi (Universitas Multimedia Nusantara, 2020)
The formation of fandom as group is caused by an existing interest for the same object. Fandom is a popular culture in the industrial society, as a way to admire certain culture. Fandom provides the evidence that audiences is an important factor in media development. Korean boyband fandom is the largest and gained highest members. At the moment, the emergence of Korean boyband fandom apprears in fan activities as the actualization of the fan’s support toward their idol. The internet has been used not only as a search engine, but also as a communication tool. The author tries to analyze the phenomenon of internet-based, namely Wattpad, and also the internet capability that enable citizen authorship. This study uses qualitative methods, by conducting interviews to obtain data. The results of this study show two factors that influence fans to write a Fan Fiction about their idols, namely internal factors amd also external factors. Keywords: Fans, Fan Fiction, Citizen Authoer, Wattpad.